Prednosti računalniško podprtega pristopa pri učenju besedišča v tujem jeziku - Retelj, Andreja (Uporabna informatika (Ljubljana), 2016)
This article deals with the implementation of computer-assisted language learning into foreign language class, with special emphasis on the development of lexical competence in German as a foreign language. The results of the pedagogical experiment, where the experimental group learned German language through a computer-assisteed approach and the control group through a communicative approach, are presented. The analysis of the results showed that the experimental group performed better in vocabulary recognition and vocabulary use. The pedagogical implications for more effective vocabulary teaching in a foreign language through computer-assisted language learning are presented.
Keywords: jezikovni pouk; tuji jeziki; besedišče; metodika pouka; računalniška orodja; računalniški programi; CALL